2018
DOI: 10.12669/pjms.346.16199
|View full text |Cite
|
Sign up to set email alerts
|

Can we link foot ulcer with risk factors in diabetics? A study in a tertiary care hospital

Abstract: Objective:Although many studies worldwide explained the risk factors for developing Diabetic Foot Ulceration (DFU), little has been done to assess medical factors in DFU formation and link them in patients of Pakistan. This study aimed to link the DFU with different risk factors.Methods:This descriptive cross-sectional retrospective study was conducted in Diabetes Endocrine and Metabolic Centre / Post Graduate Medical Institute / Lahore General Hospital. Data of all patients presenting between July 2017 to Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 15 publications
3
23
3
1
Order By: Relevance
“…Patients with DFUs were significantly overweight, have nonsignificantly lower mean arterial BP, and have high fasting serum glucose. Our findings are in agreement with Khan et al's study which found that greater BMI is significantly associated with foot ulcer while high BP or T2D is insignificantly linked to FUs [18]. Significantly high red cell distribution width value in DFUs is in agreement with other studies that demonstrated that high RDW is a marker of complicated T2D [8, 19].…”
Section: Discussionsupporting
confidence: 93%
“…Patients with DFUs were significantly overweight, have nonsignificantly lower mean arterial BP, and have high fasting serum glucose. Our findings are in agreement with Khan et al's study which found that greater BMI is significantly associated with foot ulcer while high BP or T2D is insignificantly linked to FUs [18]. Significantly high red cell distribution width value in DFUs is in agreement with other studies that demonstrated that high RDW is a marker of complicated T2D [8, 19].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, patients with diabetes taking combined medication (insulin and oral hypoglycemic agents) were 89% less likely to develop diabetic foot ulcers compared to patients with diabetes taking oral hypoglycemic agents. This contradicts with research findings conducted in: Iraq, with a cross-sectional study that showed that using a combination of insulin and oral antidiabetic agents were significantly associated with the development of DFUs, 30 Pakistan, with a cross-sectional study that states that a combination of both insulin and oral hypoglycemic agents was strongly associated with the development of diabetic foot ulcers, 19 Malaysia, with a case–control study that showed combination of both insulin and oral hypoglycemic agents were not significantly associated with DFU, 29 and Eastern Indonesia, with a case control study that states taking both insulin and oral hypoglycemic agents were not significantly associated with DFU. 18 The possible reason for this discrepancy could be due to differences in condition of the diabetes mellitus among the study participants.…”
Section: Discussionmentioning
confidence: 76%
“…Structured questionnaire adapted from different similar literature, [7][8][9][18][19][20] and standard evaluation tools for diabetic foot ulcers [21][22][23][24] were used to collect data. An intervieweradministered structured questionnaire and medical chart reviewing were carried out to collect data from the cases and controls.…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%
“…No association with gender was retrieved in some studies evaluating this parameter [ 16 , 18 , 20 ]. A male gender was associated with a higher prevalence of diabetic foot ulcers or amputations in several studies [ 17 , 27 29 ]. Our results may be explained by a more advanced age, a higher prevalence of elevated WC, and probably a lower school level in women in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated WC was associated in our study to higher risk groups. A high WC was demonstrated to be a risk factor for diabetic neuropathy [ 32 ] or for diabetic foot ulcers [ 27 , 28 ]. We could suggest the same mechanism for the elevated BMI.…”
Section: Discussionmentioning
confidence: 99%